THE SPREAD OF HOAX ON SOCIAL MEDIA IN THE NEW PARADIGM OF NATIONAL CRIMINAL LAW: A NORMATIVE STUDY OF LAW NUMBER 1 OF 2023 - Muhammad Din Al Fajar; Dwi Zahra Aini; Gabrielle Verlim Sabatini; Nadine Angelia M. Sianturi; Novran Jaenisura Pinem (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
Abstract:Spreading hoaxes through social media platforms has become a challenge for the criminal justice system in Indonesia as information technology rapidly advances. This phenomenon not only affects socio-political stability, but also poses a threat to public trust and national security. With the enactment of Law No. 1 of 2023 concerning the Criminal Code (KUHP), there has been a paradigm shift in the handling of criminal acts involving false information spread through digital media. This article uses a normative legal approach, reviewing the new criminal law provisions in the KUHP and their relevance to the spread of hoaxes on social media. The findings explain that the 2023 KUHP contains several provisions that have the potential to regulate digital content, including false news and uncertain information, while also creating new implications for freedom of expression and legal control over digital content.  These implications are important to examine so that national criminal law can effectively and proportionally address the challenges of the digital era.Keywords: Hoax, Criminal Code, Criminal Law, Social Media, Digital